Effects Of Cervical Spine Rehabilitation In Fighter Pilots: A Literature Review (Journal of Pharmaceutical Negative Results, 2023)
Years of training, practice and unique skills are required for a Fighter pilot to perform demanding and challenging operations in technologically cutting-edge aircraft. To provide a concise overview of physical fitness, muscle cross-sectional area (CSA) and GZexposure and their interaction in fighter pilots. A search of PubMed, CINHAL, Google scholar database was conducted to find relevant studies pertaining to fighter pilots, cervical spine and biomechanics. A total of 6 articles were included in the review. Exercise included stretching, ROM exercises, Acupuncture, Aerobic exercises, finger-pressure massage, resisted isometric exercises. This study provides an up-to-date overview of the current literature on the ‘Effects of cervical spine rehabilitation in fighter pilots’.